Comparing the Effectiveness of Different Dentinal Desensitizing Agents: In Vitro Study. (13th February 2021) - Farook, Mohideen S.; Mahmoud, Okba; Ibrahim, Maysara Adnan; Berkathullah, Marwah
Abstract : Objectives . To evaluate the in vitro effectiveness of desensitizing agents in reducing dentine permeability. Methods . The efficacy of desensitizing agents in reducing dentine permeability by occluding dentine tubules was evaluated using a fluid filtration device that conducts at 100 cmH2 O (1.4 psi) pressure, and SEM/EDX analyses were evaluated and compared. Forty-two dentine discs (n = 42 ) of 1 ± 0.2 mm width were obtained from caries-free permanent human molars. Thirty dentine discs (n = 30 ) were randomly divided into 3 groups (n = 10 ): Group 1: 2.7% wt. monopotassium-monohydrogen oxalate (Mp-Mh oxalate), Group 2: RMGI XT VAR, and Group 3: LIQ SiO2 . Dentine permeability was measured following treatment application after 10 minutes, storage in artificial saliva after 10 minutes and 7 days, and citric acid challenge for 3 minutes. Data were analysed with a repeated measures ANOVA test. Dentine discs (n = 12 ) were used for SEM/EDX analyses to acquire data on morphological changes on dentine surface and its mineral content after different stages of treatment. Results . Desensitizing agents' application on the demineralized dentine discs exhibited significant reduction of permeability compared to its maximum acid permeability values. Mp-Mh oxalate showed a significant reduction in dentine permeability (p < 0.05 ) when compared to RMGI XT VAR and LIQ SiO2 . On SEM/EDX analysis, all the agents formed mineral precipitates that occluded the dentine tubules. Conclusions . 2.7% wt. monopotassium-monohydrogen oxalate was significantly effective in reducing dentine permeability compared to RMGI XT VAR and LIQ SiO2 .